Translational and rotational mobility of methanol-d(4) molecules in NaX and NaY zeolite cages: A deuteron NMR investigation - Lalowicz ZT; Stoch G; Birczynski A; Punkkinen M; Ylinen EE; Krzystyniak M; Gora-Marek K; Datka J (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
Nuclear magnetic resonance (NMR) provides means to investigate molecular dynamics at every state of matter. Features characteristic for the gas phase, liquid-like layers and immobilized methanol-d(4) molecules in NaX and NaY zeolites were observed in the temperature range from 300 K down to 20 K. The NMR spectra at low temperature are consistent with the model in which molecules are bonded at two positions: horizontal (methanol oxygen bonded to sodium cation) and vertical (hydrogen bonding of hydroxyl deuteron to zeolite framework oxygen). Narrow lines were observed at high temperature indicating an isotropic reorientation of a fraction of molecules. Deuteron spin-lattice relaxation gives evidence for the formation of trimers, based on observation of different relaxation rates for methyl and hydroxyl deuterons undergoing isotropic reorientation. Internal rotation of methyl groups and fixed positions of hydrogen bonded hydroxyl deuterons in methyl trimers provide relaxation rates observed experimentally. A change in the slope of the temperature dependence of both relaxation rates indicates a transition from the relaxation dominated by translational motion to prevailing contribution of reorientation. Trimers undergoing isotropic reorientation disintegrate and separate molecules become localized on adsorption centers at 166.7 K and 153.8 K for NaX and NaY, respectively, as indicated by extreme broadening of deuteron NMR spectra. Molecules at vertical position remain localized up to high temperatures. That indicates the dominating role of the hydrogen bonding. Mobility of single molecules was observed for lower loading (86 molecules/uc) in NaX. A direct transition from translation to localization was observed at 190 K. (C) 2012 Elsevier Inc. All rights reserved.